2021
DOI: 10.3390/ijerph18115528
|View full text |Cite
|
Sign up to set email alerts
|

Prisoners as Users of Digital Health Care and Social Welfare Services: A Finnish Attitude Survey

Abstract: Prisoners are a group of people with many health and social problems. However, in prisons the use of the Internet is controlled. Thus, prisoners’ access to digital health care and social welfare services is limited. In addition, there are many cognitive and attitudinal barriers to the use of digital health care and social welfare services for prisoners. Cross-sectional survey data (N = 225) were collected from eleven prisons in different parts of Finland and analysed using linear regression analysis. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…However, the datedness of the data means that future work may build on these findings to ascertain incarceration status, ethnoracial identification, and oral health among a more recent sample of African American adults. Future work may also benefit from use of digital technologies to ascertain health status and to ensure healthcare services are successful [69]. Third, we utilized a common measure of perceived oral health status [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…However, the datedness of the data means that future work may build on these findings to ascertain incarceration status, ethnoracial identification, and oral health among a more recent sample of African American adults. Future work may also benefit from use of digital technologies to ascertain health status and to ensure healthcare services are successful [69]. Third, we utilized a common measure of perceived oral health status [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Five questions were prepared according to the concept of control by Ajzen [ 43 ]. These questions [ 50 ] were connected to the ease of use of digital services in general, perceived control of the use of digital health care and social welfare services, and confidence in learning to use new digital services. These questions were formed as statements and were evaluated on a Likert-type scale ranging from 1 (totally disagree) to 5 (totally agree).…”
Section: Methodsmentioning
confidence: 99%
“…It has also been found that digital inclusion follows some clear economic and social contours, and people with lower levels of income, employment and education are significantly less digitally included [18]. Previous studies have also pointed out that many vulnerable groups of people, such as those with mental health problems [4,6,19] and incarcerated people [20,21], are at risk of digital exclusion.…”
Section: Digital Exclusion and Inclusion Of Vulnerable Peoplementioning
confidence: 99%
“…According to van Deursen and van Dijk [9]; the first-level digital divide still remains a problem in some rich western countries because device opportunity, device and peripheral diversity, and maintenance expenses differ among segments of the population. In the case of vulnerable groups, personal circumstances and financial barriers can be factors in their digital exclusion [6], and a lack of electronic IDs can act as a barrier to access to many digital services [21]. From the beginning of the 21st century, various studies have especially highlighted the second-level digital divide related to digital skills and digital engagement [25,26].…”
Section: Digital Exclusion and Inclusion Of Vulnerable Peoplementioning
confidence: 99%